A Descriptive Study of Students’ Perceptions toward the Focus of Learning English for Specific Purposes: EAP in English Educational Field - Muhammad Yasminto, M.Pd (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2021)
The article aims to describe the students’ perceptions toward the focus of learning English for specific purposes: EAP in the English Educational Field after the students had learned English for specific purposes course. A quantitative approach was used to process the questionnaire data analyzed statistically, and a qualitative approach with a descriptive study was conducted to answer the problem of this study. The researcher used a a closed questionnaire and document of observation to the 6th-semester students of Islamic Institute of Hasanuddin, Pare Kediri in the academic year 2020/2021. The result of this study from a closed questionnaire indicates that students' perceptions toward the focus of learning ESP: EAP in the English Educational Field refers to a very strong group with 88,8% based on the score interpretation criteria. It was also proved from 34 respondents answering 15 points related to data sources that the average percentage in the strongly agreed was 56 %, agreed was 35%, doubtful was 6%, disagreed was 3%, and strongly disagreed was 0%. Therefore, it can be concluded that although the students had different perceptions, they were able to focus more on learning English for specific purposes or academic-related English or based on their field or needs. The result of observation obtained from the field as data sources was the involvement of the students’ needs towards the particular use of vocabularies and the use of tactics to accomplish the target of learning English for specific purposes/ English for academic purposes through presentation and negotiation. Keywords: Students’ perceptions, English for specific purposes, English for academic purposes